(untitled) (KASBIT Business Journal, 2021)
Despite the increasing importance of omnichannel retailing, academic research on omnichannel customer experience is still scarce, particularly those from the shopping value perspective. This paper seeks to investigate how omnichannel shopping value influences customer experience through its three distinct value dimensions within the context of fashion retail in Pakistan. The moderating role of omnichannel intensity on the relationship between shopping value dimensions and customer experience was also examined to empirically confirm the validity of the proposed model. To test hypothesized relationships, data was collected from 272 regular omnichannel customers from 18 selected fashion retail brands and analyzed using Partial Least Square Structural equation modelling. The study results revealed that omnichannel customer experience is predicted by utilitarian, hedonic and social shopping values. Unexpectedly, the results did not find any moderating effect of omnichannel intensity among shopping value dimensions and omnichannel customer experience. The findings of the study provide salient insight into how fashion retailers can utilize shopping value to enhance omnichannel customer experience. The results also offer guidance in designing and implementing effective omnichannel approaches and strategies for fashion retailers.